Determinants Revisit Intention Through Perceived Value for Tourist Visits to Tourism Destinations at Kepulauan Seribu of DKI Jakarta - Handayani, Estiningsih Tri; Limakrisna, Nandan; Muharam, Hari (UTSAHA: Journal of Entrepreneurship, 2022)
The tourism industry is important and strategic in the implementation of development in Indonesia because it is able to bring in large amounts of foreign exchange for the country. Tourist satisfaction is met will have an impact on the emergence of revisit interest (Revisit Intention), as a spontaneous response to the object of visitors because the expression of satisfaction felt during the initial visit is appropriate and even exceeds expectations. This research aims to be able to find ways and strategies to increase Revisit Intention for tourists, so that methods are found that can be recommended to interested parties through research on the variables that affect Revisit Intention, such as Promotion, Servicescape, Destination Image and Perceived Values. This research was conducted in the Kepulauan Seribu tourism destination in DKI-Jakarta with a total of 400 samples, using the Random Sampling. The research method used SEM with the LISREL program. The results of the research obtained the following data, such as (1) There is an effect Promotion on Revisit Intention (β = 0.62); (2) There is an effect Servicescape on Revisit Intention; (3) There is no effect of Destination Image on Revisit Intention (β = 0.21 ); (4) There is an effect Promotion on Perceived Value  (β =- 0.21); (5) There is an influence Servicescape on Perceived Value (        ); (6) There is no influence of Destination Image on Perceived Value (β =-0.14); and (7) There is an effect of Perceived Value on Revisit Intention (β = 0.0552).